Embedding online information resources in Virtual Learning Environments: some implications for lecturers and librarians of the move towards delivering teaching in the online environment - Margaret Markland (Information Research: An International Electronic Journal)
A small study of the use of online information resources by new Virtual Learning Environment users in a UK University provided insights into the strategies used by lecturers to select those resources, and into some of the difficulties they encountered when using online materials in their teaching. Skills training emerged as an issue for both teachers and learners, and some interesting observations were made on the working relationships of lecturing staff and librarians. The study concludes that the need for 'new alliances' frequently raised in current literature is indeed very apparent, but that to be most effective such co-operation may need to be at individual as well as at group level..